Phylogenetic analysis of DENV-1 isolated in Surabaya, Indonesia - Rahmafitria, Fistara Lesti; Mahfudhah, Dzikra Nasyaya; Sucipto, Teguh Hari; Herdyastuti, Nuniek; Anggarani, Mirwa Adiprahara; Fauziyah, Shifa; Damayanti, Mamik (Journal of Bio-Molecule Research and Engineering, 2022)
Dengue virus (DENV1-4) belongs to the Flaviviridae family, which is transmitted by the Aedes mosquito vector and is the main cause of dengue fever and dengue hemorrhagic fever. Since one of the DENV serotypes, DENV1, has become an endemic known to be circulating worldwide, including in Indonesia, it becomes necessary to carry out molecular epidemiological research using phylogenetic analysis with two methods, neighbor-joining (NJ) and UPGMA. This study aims to analyze the DENV-1 relationship and obtain information regarding the differences between those methods, including the level of accuracy. This study used one DENV-1 sequence isolated in Surabaya, aligned with similar sequences on the GenBank. The results showed two comparisons. First, in the NJ method, the DENV-1 sequence samples in Surabaya with branch length 0,000 were similar to the DENV-1 in Malaysia, and Singapore, with branch lengths 0,000; 0,002;. which belong to Genotype 1. The UPGMA method resulted in the DENV-1 sequence in Surabaya with branch length 0,000 were similar to the DENV-1 in Malaysia with with branch length 0,000, which belong to Genotype 1. Second, their level of accuracy, which is in the NJ method, the construction of phylogenetic trees is based on periodic evolutionary times. In contrast, UPGMA assumes that each sequence is found at the same evolutionary time, which makes this method less accurate than the NJ method. We can conclude that the construction and analysis of the phylogenetic tree of the DENV1 sequence isolated in Surabaya have higher similarity and accuracy using the NJ method.